Catalyst layer for membrane electrode assembly, membrane electrode assembly, and electrochemical device
Hydrophilic, porous conductive particles in the catalyst layer address catalyst poisoning issues by providing efficient proton and oxygen transport, enhancing electrochemical reaction efficiency and reducing resistance in electrochemical devices.
Patent Information
- Application Number
- JP2023097259
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
AI Technical Summary
Existing catalyst layers in electrochemical devices suffer from catalyst poisoning by ionomers, leading to decreased efficiency due to increased proton and oxygen transport resistance and layer thickness.
Incorporation of hydrophilic, porous conductive particles with interconnected pores into the catalyst layer, which act as both a proton transport path and drainage path, reducing ionomer usage and minimizing pore blockage.
Enhances electrochemical reaction efficiency by reducing proton and oxygen transport resistance while maintaining a thinner catalyst layer structure.
Smart Images

Figure 2024178823000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a catalyst layer for a membrane electrode assembly, a membrane electrode assembly, and an electrochemical device. [Background technology]
[0002] Electrochemical devices such as fuel cells use a membrane electrode assembly having an anode, an electrolyte membrane, and a cathode. The anode and cathode of the membrane electrode assembly each have a catalyst layer. The catalyst layer uses carbon particles carrying catalyst particles as an electrode catalyst. In the catalyst layer, the electrode catalyst is covered with an ionomer having ion conductivity.
[0003] Catalyst particles may be poisoned by ionomers. When catalyst particles are poisoned, their activity decreases, and the efficiency of electrochemical reactions decreases. As described in Patent Document 1, by disposing catalyst particles inside the pores of mesoporous carbon particles, it is possible to suppress the poisoning of catalyst particles by ionomers. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6931808 Summary of the Invention [Problem to be solved by the invention]
[0005] There is a need in the art for a catalyst layer suitable for improving the efficiency of electrochemical reactions. [Means for solving the problem]
[0006] The present disclosure relates to A plurality of carrier particles; A plurality of catalyst particles supported on the plurality of support particles; A plurality of conductive particles arranged in contact with the plurality of carrier particles; an ionomer attached to at least one of the carrier particles and the conductive particles; Equipped with The conductive particles are hydrophilic particles having a short axis and a long axis and a plurality of pores that are interconnected. A catalyst layer for a membrane electrode assembly is provided.
[0007] In another aspect, the present disclosure provides a method for producing a method for manufacturing a semiconductor device comprising: An anode; A cathode; an electrolyte membrane disposed between the anode and the cathode; Equipped with The cathode has a catalyst layer according to the present disclosure. A membrane electrode assembly is provided.
[0008] In yet another aspect, the present disclosure provides a method for producing a method for manufacturing a semiconductor device comprising: Provided with the membrane electrode assembly of the present disclosure, An electrochemical device is provided. Effect of the Invention
[0009] According to the technique of the present disclosure, it is possible to provide a catalyst layer suitable for improving the efficiency of an electrochemical reaction. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic cross-sectional view of a polymer electrolyte fuel cell according to a first embodiment of the present invention; [Diagram 2] Partially enlarged cross-sectional view of the cathode catalyst layer [Diagram 3] Close-up of conductive particles [Figure 4] FIG. 1 is a diagram showing the function of the cathode catalyst layer 109. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] (The knowledge and other information that formed the basis of this disclosure) At the time when the present inventors arrived at this disclosure, it was believed that in order to increase the efficiency of the electrochemical reaction in the catalyst layer of a fuel cell, it was important to form as many three-phase interfaces of the catalyst, water, and ionomer as possible from the viewpoint of supplying protons. However, in recent years, it has been found that the catalyst is poisoned by the ionomer when the ionomer comes into contact with the catalyst, resulting in a decrease in efficiency.
[0012] As described in Patent Document 1, poisoning of the catalyst by ionomer can be suppressed by disposing catalyst particles inside the pores of mesoporous carbon particles. However, since mesoporous carbon particles are bulky, the thickness of the catalyst layer increases when mesoporous carbon particles are used. When the thickness of the catalyst layer increases, the transport distance of protons and oxygen becomes longer, and the proton transport resistance and oxygen transport resistance of the catalyst layer increase.
[0013] Under these circumstances, the present inventors conducted a detailed analysis of the causes of oxygen transport resistance by direct observation with an electron microscope, electrochemical analysis, etc. As a result, they found that the excess ionomer used to form the proton transport pathway and the water generated by power generation clogged the primary pores of the catalyst layer, preventing sufficient transport of oxygen to the catalyst.
[0014] The present inventors conceived the idea that the above problems could be solved if a material having both the functions of a proton transport pathway and a drainage pathway could be introduced into the catalyst layer, which constitutes the subject matter of the present disclosure.
[0015] Hereinafter, the embodiments will be described in detail with reference to the drawings. However, in some cases, more detailed explanations than necessary may be omitted. For example, detailed explanations of already well-known matters or duplicate explanations of substantially the same configurations may be omitted.
[0016] The accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present disclosure, and are not intended to limit the subject matter recited in the claims.
[0017] (Embodiment 1) Hereinafter, the first embodiment will be described with reference to FIG. 1 to FIG.
[0018] [1-1. Configuration] 1 is a schematic cross-sectional view of a fuel cell 101 in embodiment 1. The fuel cell 101 includes a membrane electrode assembly 113, an anode separator 106, and a cathode separator 111. The membrane electrode assembly 113 is disposed between the anode separator 106 and the cathode separator 111. The fuel cell 101 is, for example, a solid polymer fuel cell.
[0019] The membrane electrode assembly 113 may also be used in other electrochemical devices, such as a hydrogen purification device for purifying hydrogen.
[0020] The membrane electrode assembly 113 includes an anode 103, an electrolyte membrane 102, and a cathode 108. The anode 103 is joined to one surface of the electrolyte membrane 102. The cathode 108 is joined to the other surface of the electrolyte membrane 102.
[0021] The electrolyte membrane 102 is disposed between the anode 103 and the cathode 108. The electrolyte membrane 102 is made of a polymer material having proton conductivity. The electrolyte membrane 102 is, for example, a membrane made of a perfluorocarbon sulfonic acid-based polymer material having sulfonic acid groups, or a hydrocarbon-based polymer material.
[0022] The anode 103 has an anode catalyst layer 104 and an anode gas diffusion layer 105. The anode catalyst layer 104 is disposed between the electrolyte membrane 102 and the anode gas diffusion layer 105. The cathode 108 has a cathode catalyst layer 109 and a cathode gas diffusion layer 110. The cathode catalyst layer 109 is disposed between the electrolyte membrane 102 and the cathode gas diffusion layer 110.
[0023] The anode catalyst layer 104 has a function of promoting an electrochemical reaction that dissociates hydrogen into protons. The anode catalyst layer 104 includes an electrode catalyst and an ionomer. The anode catalyst layer 104 may include carbon particles carrying catalyst particles and an ionomer.
[0024] The anode gas diffusion layer 105 has a function of supplying a hydrogen-containing gas to the anode catalyst layer 104 and a function of receiving electrons from the anode catalyst layer 104. The anode gas diffusion layer 105 is made of a material having gas permeability and electrical conductivity. The anode gas diffusion layer 105 has, as a main material, for example, a porous body having electrical conductivity. An example of the porous body is a carbon fiber aggregate such as carbon paper.
[0025] The cathode catalyst layer 109 has a function of promoting an electrochemical reaction that produces water from protons and oxygen. The detailed structure of the cathode catalyst layer 109 will be described later.
[0026] The cathode gas diffusion layer 110 has a function of supplying an oxidant gas to the cathode catalyst layer 109 and a function of transferring electrons to the cathode catalyst layer 109. The cathode gas diffusion layer 110 is made of a material having gas permeability and electrical conductivity. The cathode gas diffusion layer 110 has, as a main material, for example, a porous body having electrical conductivity. An example of the porous body is a carbon fiber aggregate such as carbon paper.
[0027] The anode separator 106 is provided with an anode gas flow path 107 which is a flow path for the anode gas. The cathode separator 111 is provided with a cathode gas flow path 112 which is a flow path for the cathode gas. The anode separator 106 and the cathode separator 111 are each made of a conductive material such as carbon or metal. To prevent corrosion, a corrosion-resistant coating such as a resin film or a plating film may be provided.
[0028] 2 is a partially enlarged cross-sectional view of the cathode catalyst layer 109. The cathode catalyst layer 109 has an electrode catalyst 10, conductive particles 13, and an ionomer 15. The electrode catalyst 10, the conductive particles 13, and the ionomer 15 are in contact with each other. The electrode catalyst 10 has a particle shape. The particles of the electrode catalyst 10 have a support particle 11 and a plurality of catalyst particles 12. The plurality of catalyst particles 12 are supported on the support particle 11. The plurality of support particles 11, the ionomer 15, and the plurality of conductive particles 13 form primary pores 14 of the cathode catalyst layer 109.
[0029] The ionomer 15 is an electrolyte having proton conductivity, and connects the electrode catalysts 10 to each other in a state capable of conducting protons. The ionomer 15 is attached to the support particles 11. Only a part of the surface of the support particles 11 may be covered with the ionomer 15, or the entire surface of the support particles 11 may be covered with the ionomer 15. The ionomer 15 may be attached to the conductive particles 13.
[0030] Examples of the ionomer 15 include perfluorocarbon sulfonic acid-based polymer materials having sulfonic acid groups, and hydrocarbon-based polymer materials. Perfluorocarbon sulfonic acid-based polymer materials having sulfonic acid groups have excellent proton conductivity, and are therefore suitable for the ionomer 15.
[0031] In the electrode catalyst 10, the support particles 11 are conductive. The support particles 11 are, for example, solid or porous particles. The solid particles are typically carbon particles. Examples of the solid carbon particles include carbon black particles such as ketjen black and acetylene black. In the case of the solid carbon particles, the catalyst particles 12 are supported on the surfaces thereof.
[0032] The porous particles are materials having a plurality of pores that are interconnected. The porous particles are, for example, mesoporous particles. An example of the mesoporous particles is mesoporous carbon particles. In the mesoporous particles, catalyst particles 12 are disposed inside the pores (mesopores). By disposing the catalyst particles 12 inside the pores of the mesoporous particles, it is possible to suppress the poisoning of the catalyst particles 12 by the ionomer 15.
[0033] The shape of the solid carrier particles 11 is, for example, spherical. The solid carrier particles 11 have an average particle size of, for example, 10 nm or more and 1 μm or less. The shape of the porous carrier particles 11 is, for example, spherical. The porous carrier particles 11 have an average particle size of, for example, 100 nm or more and 2 μm or less.
[0034] The average particle size of the support particles 11 is the average value of the diameters of a plurality of (e.g., 100 or more) support particles 11. The diameter of the support particles 11 can be measured using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). In the SEM image or TEM image of the electrode catalyst 10, the area of the support particles 11 is determined by image processing. The diameter of a circle having an area equal to the determined area can be regarded as the diameter of the support particles 11.
[0035] The catalyst particles 12 may be particles containing a precious metal such as platinum, a platinum alloy, etc. The platinum alloy may be an alloy of platinum and at least one selected from the group consisting of cobalt, nickel, ruthenium, and palladium.
[0036] The catalyst particles 12 may be nanoparticles. The catalyst particles 12 have an average particle size of, for example, 1 nm or more and 30 nm or less. The average particle size of the catalyst particles 12 is the average value of the diameters of a plurality of (for example, 100 or more) catalyst particles 12. The diameter of the catalyst particles 12 can be measured using a transmission electron microscope (TEM). In a TEM image of the electrode catalyst 10, the area of the catalyst particles 12 is determined by image processing. The diameter of a circle having an area equal to the determined area can be regarded as the diameter of the catalyst particle 12.
[0037] The conductive particles 13 are porous and hydrophilic particles having a short axis and a long axis. The porous particles as the conductive particles 13 have a plurality of pores that are interconnected. With such a structure and properties, the conductive particles 13 have water absorption. The water-absorbent conductive particles 13 can absorb water that is retained in the primary pores 14 of the cathode catalyst layer 109 by capillary action. In addition, the conductive particles 13 function as a proton transport path by absorbing water into the interconnected pores. Therefore, the amount of ionomer 15 used can be reduced. In particular, the amount of ionomer 15 that segregates in the primary pores 14 can be reduced. Since the primary pores 14 are unlikely to be blocked by water and ionomer 15, the oxygen transport resistance can be reduced while suppressing the proton transport resistance. As a result, the efficiency of the electrochemical reaction in the cathode catalyst layer 109 can be increased.
[0038] The conductive particles 13 being hydrophilic means that a hydrophilic functional group is provided on the surface of the conductive particles 13. Examples of the hydrophilic functional group include a hydroxyl group (-OH), a carboxyl group (-COOH), an amino group (-NH2), and a sulfo group (-SO3H). In order to provide the conductive particles 13 with hydrophilicity, the raw material of the conductive particles 13 is subjected to a surface treatment such as an oxygen plasma treatment, thereby providing the hydrophilic functional group on the surface, and the conductive particles 13 having hydrophilicity are obtained. A plurality of types of hydrophilic functional groups may be provided on the surface of the conductive particles 13. Generally, alkyl groups are present on the surface of carbon materials such as carbon fibers. Unless a special treatment is performed, these carbon materials are hydrophobic. The alkyl groups can be replaced with hydrophilic functional groups by a surface treatment such as a plasma treatment.
[0039] The presence of hydrophilic functional groups on the surfaces of the conductive particles 13 can be confirmed by energy dispersive X-ray analysis, infrared absorption spectroscopy, time-of-flight secondary ion mass spectrometry, or the like.
[0040] 3 is an enlarged view of a conductive particle 13. The conductive particle 13 has a short axis and a long axis. The short axis and the long axis are perpendicular to each other. The direction parallel to the short axis of the conductive particle 13 is defined as a first direction D1, the direction parallel to the long axis of the conductive particle 13 is defined as a second direction D2, and the direction perpendicular to both the short axis and the long axis is defined as a third direction D3.
[0041] The length L1 of the conductive particles 13 in the first direction D1 is, for example, 0.02 μm or more and 1 μm or less, and preferably 0.05 μm or more and 0.5 μm or less. The length L2 of the conductive particles 13 in the second direction D2 is, for example, 0.05 μm or more and 2 μm or less, and preferably 0.1 μm or more and 1 μm or less. The length L1 can be regarded as the length of the minor axis, and the length L2 can be regarded as the length of the major axis.
[0042] The length L2 of the conductive particle 13 in the second direction D2 is, for example, two or more times the length L1 of the conductive particle 13 in the first direction D1. The upper limit of the ratio of the length L2 to the length L1 is not particularly limited, and is, for example, 100 or less. The length L3 of the conductive particle 13 in the third direction D3 is, for example, two or more times the length L1 of the conductive particle 13 in the first direction D1. The upper limit of the ratio of the length L3 to the length L1 is not particularly limited, and is, for example, 100 or less.
[0043] The above dimensions of conductive particles 13 may be average values for any number of particles (eg, 100).
[0044] The conductive particles 13 may have a scale-like or sheet-like shape, which makes it easier for the conductive particles 13 to satisfy the above-mentioned dimensional relationship.
[0045] The shape and dimensions of the conductive particles 13 can be identified by a three-dimensional SEM observation method that combines a focused ion beam (FIB) device and a scanning electron microscope (SEM). That is, by repeatedly performing etching using the FIB and observation using the SEM in detail and reconstructing the acquired images, three-dimensional structural information of the conductive particles 13 can be obtained. From the three-dimensional structural information of the conductive particles 13, a rectangular parallelepiped with the smallest volume that circumscribes the conductive particles 13 is identified. The shortest side of the rectangular parallelepiped corresponds to the short axis of the conductive particles 13. The length of the shortest side of the rectangular parallelepiped corresponds to the length L1 of the conductive particles 13 in a first direction D1 parallel to the short axis. The longest side of the rectangular parallelepiped corresponds to the long axis of the conductive particles 13. The length of the longest side of the rectangular parallelepiped corresponds to the length L2 of the conductive particles 13 in a second direction D2 parallel to the long axis. The side perpendicular to the shortest side and the longest side corresponds to the third axis of the conductive particles 13. The length of the side perpendicular to the shortest side and the longest side corresponds to the length L3 of the conductive particle 13 in the third direction D3 parallel to the third axis.
[0046] Instead of the three-dimensional SEM, the shape and dimensions of the conductive particles 13 can also be specified by the following two-dimensional observation method. The cathode catalyst layer 109 is dissolved in a solvent such as a water-ethanol mixture to prepare a solution, and the solution is thinly applied to a substrate such as a glass plate to form a coating film. After the coating film is dried, the coating film is observed in one or more fields of view using a SEM-EDX (scanning electron microscope-energy dispersive X-ray analyzer) or a TEM-EDX (transmission electron microscope-energy dispersive X-ray analyzer). For example, the conductive particles 13 and the carrier particles 11 can be distinguished by EDX based on the presence or absence of hydrophilic functional groups. The lengths of the minor and major axes of the multiple conductive particles 11 are measured from the SEM or TEM image. In the SEM or TEM image, the short and long sides of a rectangle with the smallest area circumscribing the conductive particles 11 can be regarded as the minor and major axes.
[0047] The mode diameter of the plurality of pores 13h of the plurality of conductive particles 13 is smaller than the mode diameter of the primary pores 14 of the cathode catalyst layer 109. According to such a configuration, since the conductive particles 13 exhibit a capillary pressure larger than that of the primary pores 14, the water staying in the primary pores 14 can be easily absorbed. In this case, the blockage of the primary pores 14 by water can be further suppressed, and the oxygen transport resistance can be reduced while suppressing the proton transport resistance. As a result, the efficiency of the electrochemical reaction in the cathode catalyst layer 109 can be further enhanced.
[0048] The mode diameter of the plurality of pores 13h of the conductive particles 13 can be determined by the gas adsorption method. That is, data of the adsorption isotherm of the conductive particles 13 is obtained using a pore distribution measuring device. The adsorbed gas species is nitrogen gas. By analyzing the adsorption isotherm by the BJH (Barrett-Joyner-Halenda) method, a pore distribution is obtained. The pore distribution is, for example, a graph showing the relationship between the diameter D of the pores and the Log differential pore volume. From the pore distribution, the mode diameter of the pores, that is, the pore diameter at which the distribution density shows the maximum value in the pore distribution, can be determined.
[0049] The mode diameter of the primary pores 14 of the cathode catalyst layer 109 can be determined by the above gas adsorption method after sufficiently drying the cathode catalyst layer 109.
[0050] When the mode diameter of the plurality of carrier particles 11 is represented by X, the average value of the minor axis lengths L1 of the plurality of conductive particles 13 is represented by A, and the average value of the major axis lengths L2 of the plurality of conductive particles 13 is represented by B, A < X < B may be satisfied. According to such a configuration, the bulk density of the cathode catalyst layer 109 can be increased, and it becomes possible to form the cathode catalyst layer 109 thinly. Further, since one conductive particle 13 can connect the carrier particles 11 and the carrier particles 11, the tortuosity of the proton transport path can be reduced. In this case, since the transport distances of protons and oxygen in the cathode catalyst layer 109 can be further shortened, the oxygen transport resistance can be further reduced while further suppressing the proton transport resistance. As a result, the efficiency of the electrochemical reaction in the cathode catalyst layer 109 can be further enhanced.
[0051] The mode diameter X of the plurality of carrier particles 11 can be obtained by the above-mentioned three-dimensional SEM observation method or two-dimensional observation method. For example, the diameters of a plurality of carrier particles 11 (e.g., 100 particles) are measured by the three-dimensional SEM observation method or the two-dimensional observation method, and a histogram is created in 0.1 μm intervals. The diameter of the carrier particles 11 is the diameter of a sphere with the same volume or the diameter of a circle with the same area. In the histogram, the mode is regarded as the mode diameter.
[0052] In the cathode catalyst layer 109, the ratio of the mass of the conductive particles 13 to the mass of the carrier particles 11 is, for example, 25% or more. With this configuration, the number of contacts between the conductive particles 13 can be increased, so that the number of drainage paths and proton transport paths communicating with the inside of the cathode catalyst layer 109 can be increased. In this case, the clogging of the primary pores 14 by water can be further suppressed, so that the oxygen transport resistance can be reduced while suppressing the proton transport resistance. As a result, the efficiency of the electrochemical reaction in the cathode catalyst layer 109 can be further improved. The upper limit of the ratio is not particularly limited, and is, for example, 65% or less, and preferably 45% or less.
[0053] The above ratio can be obtained by the following method. That is, a volume V1 occupied by the plurality of carrier particles 11 and a volume V2 occupied by the plurality of conductive particles 13 are obtained for a sufficient volume region by a three-dimensional SEM observation method. A mass M1 of the plurality of carrier particles 11 is obtained by multiplying the volume V1 occupied by the plurality of carrier particles 11 by the specific gravity of the carrier particles 11. A mass M2 of the plurality of carrier particles 11 is obtained by multiplying the volume V2 occupied by the plurality of conductive particles 13 by the specific gravity of the conductive particles 13. The above ratio is the ratio of mass M2 to mass M1. "Sufficient volume" means, for example, a volume region containing 100 or more carrier particles 11 and 100 or more conductive particles 13.
[0054] In the present embodiment, the conductive particles 13 may be mesoporous carbon particles. The conductive particles 13 may include graphene meso sponge. The graphene meso sponge is a porous carbon material made of graphene and having mesopores that communicate in three-dimensional directions. Therefore, the graphene meso sponge is suitable for the conductive particles 13 in the present embodiment. The conductive particles 13 are obtained, for example, by pulverizing and / or crushing the graphene meso sponge.
[0055] It is desirable that the conductive particles 13 do not support the catalyst particles 12. However, the catalyst particles 12 that have fallen off from the electrode catalyst 10 may be attached to the conductive particles 13. In other words, "the conductive particles 13 do not support the catalyst particles 12" means that no treatment for supporting the catalyst particles 12 on the conductive particles 13 has been performed.
[0056] The conductive particles 13 can be produced, for example, by the following method.
[0057] First, a graphene meso sponge is prepared by a known method. For example, a powder of inorganic nanoparticles such as alumina nanoparticles is molded to prepare a template. Next, a carbon layer is formed on the template by a CVD method using an organic compound as a carbon source. Next, the template is selectively dissolved and removed using an acid or alkaline solution to obtain a porous carbon material. The obtained porous carbon material is heat-treated at a temperature of 1500 to 2000 degrees. This results in a graphene meso sponge.
[0058] The resulting graphene meso-sponge is crushed and / or disintegrated to obtain a powder of conductive particles 13 having the desired size and shape.
[0059] [1-2. Operation] The operation and function of the fuel cell 101 configured as above will be described below with reference to FIG.
[0060] A hydrogen-containing gas is supplied to the anode gas flow passage 107. An oxidant gas is supplied to the cathode gas flow passage 112. The oxidant gas is typically air. At the anode 103, hydrogen (H2) is converted into protons (H + ) and electrons (e - ) The protons move from the anode 103 to the cathode 108 by being conducted through the electrolyte membrane 102. The electrons move from the anode 103 to the cathode 108 through an external circuit. At the cathode 108, water (H2O) is produced by an electrochemical reaction of the protons, oxygen (O2), and electrons, as represented by the following formula (2).
[0061] H2→2H + +2e - (1) 4H + +O2+2e - →2H2O(2)
[0062] FIG. 4 is a diagram showing a schematic diagram of the function of the cathode catalyst layer 109. The conductive particles 13 contained in the cathode catalyst layer 109 absorb water generated by an electrochemical reaction. Due to the action of the conductive particles 13, the primary pores 14 are less likely to be blocked. As shown by the thin arrows, oxygen gas easily passes through the primary pores 14, so that the oxygen transport resistance is reduced. As shown by the thick arrows, the conductive particles 13 that have absorbed water function as a proton transport path, so that the proton transport resistance is also reduced. As a result, the efficiency of the electrochemical reaction in the cathode catalyst layer 109 can be increased.
[0063] [1-3. Effects, etc.] As described above, in this embodiment, the conductive particles 13 are hydrophilic particles having a short axis and a long axis, and a plurality of pores 13h that are interconnected. With this configuration, the primary pores 14 are less likely to be blocked by water and the ionomer 15, so that the oxygen transport resistance can be reduced while suppressing the proton transport resistance. As a result, the efficiency of the electrochemical reaction in the cathode catalyst layer 109 can be increased.
[0064] In addition, in the present embodiment, the mode diameter of the plurality of pores 13h of the conductive particles 13 may be smaller than the mode diameter of the primary pores 14 of the catalyst layer 109 formed by the plurality of carrier particles 11, the ionomer 15, and the plurality of conductive particles 13. According to such a configuration, since the conductive particles 13 exhibit a capillary pressure greater than that of the primary pores 14, the water retained in the primary pores 14 can be easily absorbed.
[0065] In addition, in the present embodiment, when the mode diameter of the plurality of carrier particles 11 is represented by X, the average value of the lengths of the short axes of the plurality of conductive particles 13 is represented by A, and the average value of the lengths of the long axes of the plurality of conductive particles 13 is represented by B, A < X < B may be satisfied. According to such a configuration, the bulk density of the cathode catalyst layer 109 can be increased, and the cathode catalyst layer 109 can be formed thinly.
[0066] In addition, in the present embodiment, the ratio of the mass of the plurality of conductive particles 13 to the mass of the plurality of carrier particles 11 may be 25% or more. According to such a configuration, since the contacts between the conductive particles 13 can be increased, the drainage paths and proton transport paths communicating inside the cathode catalyst layer 109 can be increased.
[0067] In addition, in the present embodiment, the carrier particles 11 may be mesoporous particles, and the catalyst particles 12 may be disposed inside the pores of the mesoporous particles. By disposing the catalyst particles 12 inside the pores of the mesoporous particles, poisoning of the catalyst particles 12 by the ionomer 15 can be suppressed.
[0068] In addition, in the present embodiment, the conductive particles 13 may contain graphene mesosponge. Graphene mesosponge is suitable for the conductive particles 13.
Industrial Applicability
[0069] The technology of the present disclosure is useful for electrochemical devices such as secondary batteries, fuel cells, and hydrogen purification devices.
Explanation of Signs
[0070] 10 Electrocatalyst 11 Carrier particles 12 Catalytic particles 13 Conductive particles 13h pores 14 Primary pores 15 Ionomer 101 Fuel Cell 102 Electrolyte membrane 103 Anode 104 Anode catalyst layer 105 Anode gas diffusion layer 106 Anode separator 107 Anode gas flow path 108 Cathode 109 Cathode catalyst layer 110 Cathode gas diffusion layer 111 Cathode separator 112 Cathode gas flow path 113 Membrane electrode assembly
Claims
1. A plurality of carrier particles; A plurality of catalyst particles supported on the plurality of support particles; A plurality of conductive particles arranged in contact with the plurality of carrier particles; an ionomer attached to at least one of the carrier particles and the conductive particles; Equipped with The conductive particles are hydrophilic particles having a short axis and a long axis and a plurality of pores that are interconnected. Catalyst layer for membrane electrode assembly.
2. a mode diameter of the plurality of pores of the conductive particles is smaller than a mode diameter of primary pores of the catalyst layer formed by the plurality of support particles, the ionomer, and the plurality of conductive particles; The catalyst layer for a membrane electrode assembly according to claim 1 .
3. When a mode diameter of the plurality of carrier particles is represented by X, an average value of the lengths of the minor axes of the plurality of conductive particles is represented by A, and an average value of the lengths of the major axes of the plurality of conductive particles is represented by B, A<X<B is satisfied. The catalyst layer for a membrane electrode assembly according to claim 1 .
4. The ratio of the mass of the conductive particles to the mass of the carrier particles is 25% or more. The catalyst layer for a membrane electrode assembly according to claim 1 .
5. the carrier particles are mesoporous particles, The catalyst particles are disposed within the pores of the mesoporous particles. The catalyst layer for a membrane electrode assembly according to claim 1 .
6. the conductive particles comprise graphene mesosponge; The catalyst layer according to claim 1 .
7. An anode; A cathode; an electrolyte membrane disposed between the anode and the cathode; Equipped with The cathode comprises a catalyst layer according to claim 1. Membrane electrode assembly.
8. A membrane electrode assembly according to claim 7, Electrochemical devices.
Citation Information
Patent Citations
Electrode catalyst for fuel cell, electrode catalyst layer of fuel cell, membrane / electrode assembly and fuel cell
JP6931808B1
